2022
DOI: 10.1111/apt.17223
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adaptations and outcomes of patients experiencing inflammatory bowel disease flares during the early COVID‐19 pandemic: the PREPARE‐IBD multicentre cohort study

Abstract: Summary Background The COVID‐19 pandemic offered a unique opportunity to understand inflammatory bowel disease (IBD) management during unexpected disruption. This could help to guide practice overall. Aims To compare prescribing behaviour for IBD flares and outcomes during the early pandemic with pre‐pandemic findings Methods We performed an observational cohort study comprising patients who contacted IBD teams for symptomatic flares between March and June 2020 in 60 National Health Service trusts in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Furthermore, the question of inducing flares through vaccine-triggered immune activation arose, even though it has never been recorded for routinely administrated vaccines [ 12 , 19–22 ]. SARS-CoV-2 infections were identified as possible IBD flare inducers, further increasing the fear of SARS-CoV-2 vaccination–induced flares [ 5 , 23 ]. Eighty percent of hesitant IBD patients reported that their health care provider’s recommendation was important in their decision [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the question of inducing flares through vaccine-triggered immune activation arose, even though it has never been recorded for routinely administrated vaccines [ 12 , 19–22 ]. SARS-CoV-2 infections were identified as possible IBD flare inducers, further increasing the fear of SARS-CoV-2 vaccination–induced flares [ 5 , 23 ]. Eighty percent of hesitant IBD patients reported that their health care provider’s recommendation was important in their decision [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We thank Haydek and Scott for their thoughtful editorial about our PREPARE‐IBD study 1,2 . As they highlighted, there were reassuring signals regarding clinical outcomes during the pandemic despite the significant challenges faced by clinical teams.…”
mentioning
confidence: 98%
“…We thank Haydek and Scott for their thoughtful editorial about our PREPARE‐IBD study. 1 , 2 As they highlighted, there were reassuring signals regarding clinical outcomes during the pandemic despite the significant challenges faced by clinical teams. This suggests that further evaluation of the adaptations made in diagnostic, monitoring and treatment approaches will be useful, both as we learn to live with SARS‐CoV‐2 and in anticipation of future pandemics.…”
mentioning
confidence: 99%
“…Saifuddin et al 3 performed a retrospective observational cohort study evaluating 1864 patients with IBD from 60 UK National Health Service trusts who self‐reported IBD‐related symptoms during the first 4 months of the COVID pandemic compared to patients reporting symptoms prior to the pandemic. Prescribing and monitoring patterns were assessed, as were 3‐month outcomes including steroid‐free remission, hospital admission and management of flares.…”
mentioning
confidence: 99%